Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006424.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Culturally appropriate health education for type 2 diabetes mellitus in ethnic minority groups

Abstract: Culturally appropriate diabetes health education appears to have short term effects on glycaemic control and knowledge of diabetes and healthy lifestyles. None of the studies were long-term, and so clinically important long-term outcomes could not be studied. No studies included an economic analysis. The heterogeneity of studies made subgroup comparisons difficult to interpret with confidence. There is a need for long-term, standardised multi-centre RCTs that compare different types and intensities of cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(174 citation statements)
references
References 137 publications
7
160
2
5
Order By: Relevance
“…We identified 14,841 references for screening, of which 17 were included in this meta-review [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] ( Figure 10). A total of 322 RCTs were included within these 17 systematic reviews.…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 14,841 references for screening, of which 17 were included in this meta-review [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] ( Figure 10). A total of 322 RCTs were included within these 17 systematic reviews.…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
“…Four reviews were identified which focused on culturally specific interventions. 103,105,108,112 Two of these looked at a specific ethnic minority: South Asians living in western countries 105 and Latinos living in the USA. 112 The remaining two reviews looked more broadly at interventions which were culturally or religiously tailored.…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Most current diabetes education programs are knowledge based and have emphasis on lifestyle changes, self-care and active participation in disease management. 1,2,8 These education sessions were often delivered to a group of patients. 1,2.8 There is little information about the effect of individualized and personality specific diabetes education on the management outcomes of T2DM.…”
Section: Introductionmentioning
confidence: 99%